Rib fracture treatment and management - Alzahrani, Yasser; Alhazmi, Mohammad; Al Ibrahim, Mohammed; Alzahrani, Hani; Calacattawi, Abdullah; Alosaimi, Amirah; Alkahtani, Abdullah; Aljumah, Mohammad; Surrati, Abdulmalik; Saan, Ibrahim (International Journal Of Community Medicine And Public Health, 2018)
Simple rib fractures are the most common injury sustained following blunt chest trauma, accounting for more than half of thoracic injuries from non-penetrating trauma. Severe blunt injury to the chest continues to be one of the leading causes of morbidity and mortality in both young and old trauma victims. We conducted the current meta-analysis using a comprehensive search of EMBASE, MEDLINE, PubMed, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials till 01 February 2018 for randomized controlled trials that compared operative-to-non-operative administration in flail chest patients. We identified 6 studies that could be included in the meta-analysis. In total, there were 129 patients receiving operative management compared to 152 patients in the non-operative management group. A positive effect of surgical rib fracture fixation was observed for pneumonia rate [ES 0.43, 95% CI 0.29, 0.72], duration of ICU stay [ES −4.54 days 95% CI (−6.02, −1.89) p>0.0001]. No significant difference was noted in mortality rate [ES 0.55, 95% CI (0.14, 2.44)] between the two treatment strategies. Operative management of flail chest might, therefore, be a promising treatment strategy that could not only improve patient’s outcome, but also lower treatment costs. These observations might be of value for surgeons treating patients with flail chest.